Persepsi Aparat Penegak Hukum Tentang Implemenasi Asas Lex Specialis Derogat Legi Generali Dalam Sistem Peradilan Pidana - Shinta Agustina Iwan Kurniawan Nani Mulyati (Masalah-Masalah Hukum, 2012)
Abstract Due to the complexity of regulations on criminal law, one single  action  could breach directly two or more criminal acts. In such cases, the principle of lex specialis derogat legi generali must be implemented, as stipulated in article 63 (2) of the  Criminal Code. This principle required the two acts should regulate the same object or action, otherwise it could not be implemented although the offender seem has breached two acts arised from a single action. In this time being  the implementation of this principle  often rised an unsatisfaction due to its inconsistency that has rised disparity of sentencing. The different perception of the law enforcement officers on the meaning of particularly criminal law, the cases in which the principle should be implemented, and the model of charging that should be used, are several causes of the inconcistency implementation. Keywords: Lex Specialis Derogat Legi Generali,  particular criminal law, and perception of law enforcement officer. Abstrak Tindak pidana yang terjadi  dalam masyarakat seringkali melanggar beberapa ketentuan hukum pidana di luar KUHP (hukum pidana khusus) sekaligus. Penegakan hukum terhadap kasus demikian sering tidak memuaskan karena penerapan asas lex specialis derogat legi generali yang inkonsisten, sehingga terjadi disparitas pidana. Pemahaman aparat penegak hukum yang berbeda tentang apa yang dimaksud hukum pdiana khusus, tahapan penerapannya, dan bentuk surat dakwaan yang sesuai bagi penanganan perkara pidana yang demikian menjadi penyebab terjadinya inkonsistensi penegakan hukum tersebut. Kata Kunci: Asas Lex Specialis Derogat Legi Generali, Hukum Pidana Khusus, dan persepsi penegak hukum.